Surface Exclusion Revisited: Function Related to Differential Expression of the Surface Exclusion System of Bacillus subtilis Plasmid pLS20 - Gago-Córdoba, César; Val-Calvo, Jorge; Miguel-Arribas, Andrés; Serrano, Ester; Singh, Praveen K.; Abia, David; Wu, Ling Juan; Meijer, Wilfried J. J. (Frontiers in Microbiology, 2019)
During conjugation a genetic element is transferred from a bacterial donor to a recipient cell via a connecting channel. It is the major route responsible for the spread of antibiotic resistance. Conjugative elements can contain exclusion system(s) that inhibit its transfer to a cell already harboring the element. Our limited knowledge on exclusion systems is mainly based on plasmids of Gram-negative bacteria. Here we studied the conjugative plasmid pLS20 of the Gram-positive Bacillus subtilis. We demonstrate that pLS20 contains an exclusion system and identified the single gene responsible for exclusion, named sespLS20, which is embedded in the conjugation operon. SespLS20 is the founding member of a novel family of surface exclusion proteins encoded by conjugative elements of Gram-positive origin. We show that the extent of surface exclusion correlates with the level of sespLS20 expression, and that sespLS20 is expressed at basal low-levels in all donor cells but becomes highly expressed in conjugating cells. Accordingly, the transfer of pLS20 from a conjugation-primed donor cell to an un-primed or conjugation-primed donor is inhibited moderately and very efficiently, respectively. The consequences of this differential regulation, which appears to be a conserved feature of surface exclusion systems of Gram-positive and Gram-negative origin, are discussed.